2009
DOI: 10.1088/0004-637x/707/1/l6
|View full text |Cite
|
Sign up to set email alerts
|

Mirror and Point Symmetries in a Ballistic Jet From a Binary System

Abstract: Models of accretion disks around a star in a binary system predict that the disk will have a retrograde precession with a period a factor of ∼10 times the orbital period. If the star+disk system ejects a bipolar outflow, this outflow will be subject to the effects of both the orbital motion and the precession. We present an analytic, ballistic model and a three-dimensional gasdynamical simulation of a bipolar outflow from a source in a circular orbit, and with a precessing outflow axis. We find that this combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 19 publications
4
63
2
Order By: Relevance
“…Anglada et al (2007), using the formulation given by Masciadri & Raga (2002), analyze the extreme cases where the dominant effect is either the orbital motion of the jet source in a binary system, or the precession of the ejection axis of the jet because of tidal interactions between the disk where the jet originates and a companion star. Here, we develop the work of Raga et al (2009b), and we consider a physical system, in which both the orbital motion and precession can be present simultaneously, to fit the HH 30 jet and counterjet wiggling shape.…”
Section: Jet Wigglingmentioning
confidence: 99%
“…Anglada et al (2007), using the formulation given by Masciadri & Raga (2002), analyze the extreme cases where the dominant effect is either the orbital motion of the jet source in a binary system, or the precession of the ejection axis of the jet because of tidal interactions between the disk where the jet originates and a companion star. Here, we develop the work of Raga et al (2009b), and we consider a physical system, in which both the orbital motion and precession can be present simultaneously, to fit the HH 30 jet and counterjet wiggling shape.…”
Section: Jet Wigglingmentioning
confidence: 99%
“…As we have pointed out in the past (Masciadri & Raga 2002;Raga et al 2009), an orbital motion of the jet source can result in mirror symmetries of the outflow lobes. However, the relatively low orbital velocities possible for the sources of observed mirror-symmetric pPNs cannot be responsible for the large angular deviations of their outflow lobes (Velázquez et al 2013;Riera et al 2014).…”
Section: Discussionmentioning
confidence: 75%
“…For orbital periods less than the precession period, these authors found that mirror symmetry is observed close to the central source with respect to the orbital plane, while point-symmetric morphologies prevail at larger distances (Masciadri & Raga 2002;Raga et al 2009). The influence of the orbital motion on the line emission of these objects was analyzed by Haro-Corzo et al (2009).…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, the mirror-symmetry (or multipolar geometry) may be caused by the orbital motion of a binary system (i.e., the jet source is moving in an orbit around a stellar companion) (Haro-Corzo et al 2009;Raga et al 2009). Haro-Corzo et al (2009) computed three-dimensional hydrodynamical simulations of a jet launched from the secondary star of a binary system.…”
Section: Discussionmentioning
confidence: 99%